Impact of Prolonged COVID-19 Lockdown on Body Mass Index, Eating Habits, and Physical Activity of University Students in Bangladesh: A Web-Based Cross-Sectional Study - Hossain, Md. Jamal; Ahmmed, Foyez; Khan, Md. Robin; Rashid, Parisa Tamannur; Hossain, Sorif; Rafi, Md. Oliullah; Islam, Md. Rabiul; Mitra, Saikat; Emran, Talha Bin; Islam, Fahadul; Alam, Morshed; Sarker, Md. Moklesur Rahman; et al. (Frontiers in Nutrition, 2022)
The study aims to evaluate the changes in BMI, dietary patterns, and the extent of physical activities among university students following the prolonged COVID-19 lockdown in Bangladesh. A cross-sectional web-based survey was conducted between July 10 to August 10, 2021, through a pre-designed Google Form to collect the data required for assessing the changes in BMI, eating behaviors, and physical activity between “before” and “during” the COVID-19 lockdown among the Bangladeshi university students (age: ≥ 18 years). Informed consent was electronically obtained from each participant, and a simple snowball technique was employed during the sample recruitment. Univariate (frequency and percentage distribution), paired t-test, bivariate (chi-square test), and multivariate (multinomial and binary logistic regression) analyses were consecutively applied to analyze the collected clean data set. Among the total participants (n = 1,602), 45.1%, 55.6%, and 14.2% were female, 22 to 25 years' age, and regular smokers, respectively. The current BMI (mean ± standard deviation, SD) following the prolonged COVID-19 lockdown was 23.52 ± 7.68 kg/m2 which was 22.77 ± 4.11 kg/m2 during the pre-lockdown period (mean difference = 0.753; p < 0.001). The multinomial logistic regression found a significant impact of gender, age, monthly family income, university type, eating larger meals/snacks, and physical exercise on overweight/obesity. Besides, the female students, and who kept their eating habits constant were more likely to be underweight. Additionally, the binary logistic regression analysis found that the students from private universities, urban areas, wealthier families, and who were taking larger meals/snacks were substantially more physically inactive.